MAM, uma historia sem fim - Bianchi, Ronaldo (2006)
The study of branding has gained different concepts and functions by the authors who had studied it. Today, we now that the brand is an important item of market differentiation which has an identity and an environment that the companies must be adapt. The brand identity it encloses not only who consumes it, but also encloses the public who work and sell the brand. The trademark is not only important for the corporative world, in the last few years the mark has became important in the cultural environment as a new form of businesses. In the cultural marketing, notices a procedure standard to start and sell new projects, as well as giving the continuation. Firstly, a unit for the construction of projects is mounted, with the ready project it is important to make a research for sponsors and to present the project with a media plan to close the selling of the business. In this work, we will analyze the Museum of Modern Art of São Paulo (MAM) as an important trademark in the Brazilian cultural scene. The work tells the history of MAM, by means of its different administrations. In the first administration of Ciccillo Matarazzo, the MAM was consecrated by the society, media and artists. In its second administration, the museum survived with few resources, because Ciccillo Matarazzo had left to finance the museum. In its third administration had Dinah Lopes Coelho as a leader who produced the Panoramas de Arte Brasileira and reestablish the brand prestige of The Museum of Modern Art of São Paulo. The fourth administration of MAM was headed by Aparício Basílio Da Silva, in this administration, the museum passed again for financial difficulties that had been only cured in the administration of Eduardo Levy, who inaugurates the phase of professionalism of the museum, which goes to stabilize itself in the management of Milu Villela. The Milu Villela s management has strong corporative characteristics; in this administration the professionalism of MAM is evident which acquired corporative and professional partnerships of diverse areas. We have analyzed the pointers of performance of the museum that we considered basic for the construction of the trademark MAM, are it: the headquarters, the quantity, financing, expositions, public, press repercussion, awards and the application of the brand